Social Factors Forming Differences in the Discourse on the Quality of School Education - Сенина, Наталья; Мерцалова, Татьяна; Заир-Бек, Сергей (Voprosy obrazovaniâ, 2024)
The quality of school education is not only a normative, but also a social concept that is a part of the actual communicative field for almost all social groups. The attitude to the quality of education and measures aimed at improving it make up a complex and ambiguous structure, which is capable of either uniting people belonging to different professions, living in different territories, supporting different political views, or separating people who belong to seemingly homogeneous social groups. This publication contributes to the study of factors influencing different perceptions of the quality of school education typical for different stakeholders and their attitude to measures aimed at improving it. Basing on the results of the qualitative study, which embraced representatives of various social groups interested in the quality of school education, its discursive analysis is presented from the standpoint of modern social theories. Particular emphasis is placed on identifying the reasons for the recorded differences in the views of different social groups about the quality of school education, which ultimately allows us to come up with methods for predicting their behavior in relation to the managerial measures undertaken by the state for improving the quality of school education.